PENURUNAN KADAR LOGAM KADMIUM MENGGUNAKAN ADSORBEN NANO ZEOLIT ALAM ACEH - Cut Raziah; Zerlinda Putri; Atika Rahmi Lubis; Sofyana; Zuhra; Suhendrayatna; Sri Mulyati (Jurnal Teknik Kimia USU, 2017)
The presence of Cadmium (Cd) in groundwater is an issue that needs serious handling as it causes problems to human health. The removal of Cadmium (Cd) can be done by various methods such as adsorption, oxidation, filtration, and many more. In this study, the method used was adsorption using Aceh natural zeolite. This process was expected to reduce Cd metal as effectively as possible. The adsorption was conducted by varying contact time, adsorbent dosage, pH and initial concentration of Cd metal. The crystallized Aceh natural zeolite was characterized by X-Ray Fluorescence (XRF) with Si/Al zeolite ratio of 4.36 %. The concentration of Cadmium in water was analyzed by means of Atomic Adsorption Spectrophotometer (AAS) standard AA 630. The results showed that the adsorption of cadmium in water solution by Aceh natural zeolite occurred according to the Freundlich adsorption model. While the adsorption kinetic from the process was found to be a pseudo second order with k2 value of 1.53.